PROCESELE INOVAŢIONALE - OBIECT AL MANAGEMENTULUI STRATEGIC - USM ADMIN (Moldova State University, 2007)
An innovative process could be seen as people, organizations, involved in the process of changing of school. All the actions can lead to obtaining the needed results. The directional and organized character of the innovative activity in the school can be obtained on the basis of an intelligent construction of an active structure of the innovative process, taking into consideration the structure of each action. The following components of this structure: motives - goals - tasks - forms - methods - results.